2014
DOI: 10.1097/coh.0000000000000038
|View full text |Cite
|
Sign up to set email alerts
|

The emerging face of the HIV epidemic in the Middle East and North Africa

Abstract: Purpose of reviewA volume of quality HIV data has materialized recently in the Middle East and North Africa (MENA). This review provides a thematic narrative of the patterns of HIV infection transmission in this region in light of these data.Recent findingsTens of integrated bio-behavioral surveillance surveys among hard-to-reach key populations at higher risk have been conducted in MENA in the recent years. Many of the studies reported appreciable and growing HIV prevalence. A few studies found alarming preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 20 publications
3
72
2
Order By: Relevance
“…In addition, clinic-based cohort studies have suggested that patients are presenting late with AIDS. It is hoped that with better surveys, and more programmatic work to reduce the stigma associated with HIV/AIDS, the epidemic in this region will be better understood and reduced [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, clinic-based cohort studies have suggested that patients are presenting late with AIDS. It is hoped that with better surveys, and more programmatic work to reduce the stigma associated with HIV/AIDS, the epidemic in this region will be better understood and reduced [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The data have been identified through comprehensive systematic searches of literature, conducted as part of the MENA HIV/AIDS Epidemiology Synthesis Project [11,23] and the MENA HCV Epidemiology Synthesis Project [24]. Data collection in the MENA HIV/AIDS Epidemiology Synthesis Project started in mid-2003 with the mandate to collect and synthesize all available data on HIV, sexually transmitted infections, and sexual behaviour in MENA through a series of systematic sub-studies focused on different aspects of the HIV epidemic [10,11,15,23,2528]. Data collection on the MENA HCV Epidemiology Synthesis Project started in April 2011 with the mandate to characterize HCV epidemiology in MENA and estimate country-specific population-level HCV prevalence through a series of systematic sub-studies focused on sub-regional analyses [20,24,2936].…”
Section: Methodsmentioning
confidence: 99%
“…The search terms used in the literature searches included broad geographic, infection, and epidemiological qualifiers to ensure inclusiveness, as can be seen in different sub-studies of the two Synthesis Projects [10,11,15,20,2326,2838]. …”
Section: Methodsmentioning
confidence: 99%
“…In addition, scarcity of gender-sensitive programs and lack of systematic approach in development of national guidelines hinder enactment of new treatment strategies in MENA [4,5,13,14] . HIV epidemic is characterized by rising incidence and prevalence rates among key at-risk populations, specifically among people who inject drugs (PWIDs) [12] . Hence the co-infections that are diagnosed more commonly among these population groups require particular attention in the implementation of the ART guidelines [15,16] .…”
Section: Introductionmentioning
confidence: 99%
“…From a social perspective, the cultural context that prohibits HIV related high-risk behaviors encourages ubiquitous stigma that affects access to available services in the MENA countries [4][5][6][7] . Availability and allocation of resources, on the other hand, has been threatened by ongoing conflicts and high rates of migration [8][9][10][11][12] . From a public health perspective, in many countries of the MENA lack of integrated data on HIV incidence rates and disease progression among known patients requires to be increased [8] .…”
Section: Introductionmentioning
confidence: 99%